Analisis Penyimpangan Fasa dan Sifat Mekanik pada Baja Paduan Hasil Pengecoran Konvensional di Bengkel Tenayan Pekanbaru - Agung Laksono Yudho; Farhan Anggriawan (Universitas Muhammadiyah Metro, 2026)
This research addresses metallurgical challenges in engineering the microstructure of as-cast products caused by the slow cooling rates and non-uniform phase distribution inherent to sand casting. This study aims to evaluate the effect of alloying elements on the microstructural and mechanical properties of as-cast steel specimens (SP1, SP2, and SP3). Characterization was performed via metallographic observation of dendritic morphology and flake graphite distribution, followed by micro-Vickers hardness and tensile elongation testing. The results reveal an inversely proportional trade-off between surface hardness and material strain capability. Specimen SP2 exhibited the highest hardness 397.77 + 9.02 HV due to a rigid, interlocking dendritic network, which heightened the internal notch sensitivity of the graphite phase and triggered premature brittle fracture with a minimum elongation of 8.1 %. Conversely, SP1 yielded the best matrix homogeneity and lowest hardness 316.00 + 1.25 HV, effectively distributing local stresses to achieve the highest elongation 17.3 %, while SP3 showed a transitional behavior. Future work recommends utilizing an induction furnace and applying post-casting heat treatment to optimize alloy toughness.